The Facial Displays of Leaders (Springer International Publishing, 2018)
This book provides a multifaceted analysis of how the human face drives many of our most important social behaviors. People perceive the identities, genders, and attractiveness of others from the many different faces they see every day. There has been great deal of research on the psychology, neuropsychology and neuroscience of how these perceptions are formed. However the facial displays of leadership, with their almost ubiquitous role in our social lives, remain largely unexplored. Carl Senior argues that perhaps now more than ever, it is crucial to understand how facial displays communicate leadership abilities. This book brings together perspectives from a range of international experts across a variety of fields including social psychology, organisational sciences and the study of primates, with the aim to further our understanding of this fundamental social force. Scholars and professionals, as well as anyone interested in learning more about how the face is used to drive our perception of leadership, will find this book of great interest. .